Effectiveness of a parent-training program in Spain: reducing the Southern European evaluation gap - Noelia Vázquez; M. Cruz Molina; Pilar Ramos; Lucía Artazcoz (Elsevier, 2019)
Objective: We implemented and evaluated the Parenting Skills Program for families in Spain 1) to examine differences in parenting skills, social support, children's behaviours and parental stress pre, immediately post and six months post intervention and 2) to identify mechanisms by which the intervention is related to changes in the four outcomes examined. Methods: Quasi-experimental study design with pre (T0), post (T1), a follow-up (T2) and no control group, complemented by a qualitative study was used. The outcome variables were social support, parenting skills, parental stress and children's behaviours. 216 parents completed pre and post questionnaire and 130 parents the follow-up questionnaire. 39 professionals and 34 parents participated in 17 interviews and 5 discussion groups. Results: Compared with T0, all four outcomes improved significantly at T1. 76% of the participants improved parenting skills and 61% social support. 56% reduced children's negative behaviours and 66% parental stress. All outcomes maintained this significant improvement at T2. Parents and professionals describe different changes in parents' parenting skills, stress and social support after participation in the PSP, and in their children's behaviours. Some subcategories emerged after analysing parents' and professionals' discourses. Conclusions: This study describes positive parenting effects on participants of a parent-training program in Spain, which is a country where implementation and evaluation of these kind of interventions is an incipient issue. Resumen: Objetivo: Se introdujo y evaluó el Programa de Habilidades Parentales para familias a fin de: 1) examinar las diferencias en cuanto a habilidades parentales, apoyo social, comportamientos infantiles y estrés parental preintervención, inmediatamente después y 6 meses después de la intervención, y 2) identificar los mecanismos que explican los cambios generados por la intervención para las cuatro variables examinadas. Método: Estudio cuasiexperimental con pre (T0), post (T1) y seguimiento (T2), sin grupo control, complementado con un estudio cualitativo. Variables: apoyo social, habilidades parentales, estrés parental y comportamientos infantiles. Completaron el cuestionario pre y post 216 padres/madres, y 130 el de seguimiento. Treinta y nueve profesionales y 34 padres/madres participaron en 17 entrevistas y cinco grupos de discusión. Resultados: Comparado con T0, las cuatro variables mejoraron significativamente en T1. El 76% de los participantes mejoraron las habilidades parentales y el 61% el apoyo social. El 56% redujo los comportamientos infantiles negativos y el 66% el estrés parental. Las variables mantuvieron significativa la mejora en T2. Padres/madres y profesionales describieron cambios en las cuatro variables tras participar en el Programa de Habilidades Parentales. Surgieron subcategorías tras el análisis discursivo. Conclusiones: Este estudio describe efectos positivos en la parentalidad de los participantes en un programa de educación parental español, siendo este un país donde la introducción y la evaluación de este tipo de programas son incipientes. Keywords: Parent-training, Program evaluation, Social support, Parenting skills, Parental stress, Child behaviour, Palabras clave: Educación parental, Evaluación de programas, Apoyo social, Habilidades parentales, Estrés parental, Comportamiento infantil